Hubungan Antara Kepemimpinan Dan Disiplin Kerja Dengan Kinerja Petugas Surveilans Diare Di Dinas Kesehatan Kota Salatiga - RUSILAWATI, ENNY (2012)
Dinas Kesehatan Kota Salatiga as part of the government agency in charge of organizing Salatiga prevention and eradication of diseases, and environmental health efforts in the community in order to achieve Healthy Salatiga. One indicator of an employee at Dinas Kesehatan Kota Salatiga can be good demonstrated by the quality of the employees working on the surveillance is satisfactory. This study aimed to determine the relationship between leadership and job performance disciplines diarrhea surveillance officer in Dinas Kesehatan Kota Salatiga. This type of research is descriptive analytic cross sectional design. The subjects were Public Health Surveillance Officer. The number of samples in this study were as many as 39 people were obtained by the formula Slovin with proportional random sampling technique sampling. The data analysis tools with the Spearman-rank correlation test. The results of data analysis showed significant relationship between leadership and performance surveillance officer (p value=0.001), and there was a significant relationship between job performance disciplines surveillance officer (p value=0.000).